Ecological Adaptation as a Form of SDG's Achievement Attempts for The Community in Conflict Areas through Poverty Alleviation - Kriswantriyono, Agit (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The effect of the conflict in Poso on the community agricultural activity is significant. The objective of this research is to observe the community adaptive behaviour in responding to the environmental changes. The research was carried out in three villages in Poso. The data was collected through interview, and the analysis carried out through cybernatic analysis. The research result waspresented that most of the community was pro-actively adapted, to adjusted of the plantation agriculture pattern to the basic crop agriculture. The factors that influenced the community adaption strategy were the activities in the program, education, and social status. The adaption behaviour had also a high corelation with the level of independency, whereas the higher the level of indepedency people, the more adaptive the behaviour is. There are relation between the village durability index with the village typology, whereas a village with a typology of mountainous areas and far from urban areas, its environmental tenacity index is very good. While villages with a typology of community diversity are high, have a good social tenacity index. With regard to SDG's achievements, the empowerment program in Poso has achieved SDG'1, 5, 10 and SDG's 16.